POSSIBILITIES OF USING THE CLASTER METHOD IN FORMING A SENSE OF NATIONAL PRIDE - Jumaev Abdilhakim Turdievich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the use of the cluster methad in thi formation of a sense of national pride studentes.